2022
DOI: 10.1038/s41598-022-26090-5
|View full text |Cite
|
Sign up to set email alerts
|

Systematic analysis of healthcare big data analytics for efficient care and disease diagnosing

Abstract: Big data has revolutionized the world by providing tremendous opportunities for a variety of applications. It contains a gigantic amount of data, especially a plethora of data types that has been significantly useful in diverse research domains. In healthcare domain, the researchers use computational devices to extract enriched relevant information from this data and develop smart applications to solve real-life problems in a timely fashion. Electronic health (eHealth) and mobile health (mHealth) facilities al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 187 publications
(130 reference statements)
0
6
0
1
Order By: Relevance
“…Ni et al reported a 450% increase in efficacy of clinical trial pre-screening using electronic health record and not a patient registry, despite the fact that 10% of eligible patients were missed in the process [ 101 ]. More globally, data-driven technologies and strategies are more and more being reported in the literature, whether it is supporting prevention, diagnosis, or decision-making [ 103 106 ]. Such strategies’ impact on time optimization and associated cost reduction could be of great aid both to small trial centers working with limited staff and resources, and bigger trial centers dealing with a large volume of patients and trials.…”
Section: Discussionmentioning
confidence: 99%
“…Ni et al reported a 450% increase in efficacy of clinical trial pre-screening using electronic health record and not a patient registry, despite the fact that 10% of eligible patients were missed in the process [ 101 ]. More globally, data-driven technologies and strategies are more and more being reported in the literature, whether it is supporting prevention, diagnosis, or decision-making [ 103 106 ]. Such strategies’ impact on time optimization and associated cost reduction could be of great aid both to small trial centers working with limited staff and resources, and bigger trial centers dealing with a large volume of patients and trials.…”
Section: Discussionmentioning
confidence: 99%
“…This work identifies several key features and optimal management designs proposed in the area of medical big data analysis to achieve efficacy in disease diagnosis, suggesting that the results of this systematic work should adjust advanced hybrid machine learning-based models and cloud computing applications to improve treatment quality. Therefore, this study will help policymakers, researchers, and practitioners to encourage the development of advanced disease diagnosis models, as well as to present the quality of improved treatment mechanisms for patients ( 41 ). While the issue of property rights over the value of personal information is being discussed, the reality is that data cannot provide clear valuation criteria for intangible assets and legal grounds for them.…”
Section: Discussionmentioning
confidence: 99%
“…In a study by Khan, Khan & Nazir (2022) comprehensive and systematic research spanning articles from 2011 to 2021 focused on analyzing the health care domain in disease diagnosis using data analytics. The findings suggested that integrating advanced hybrid machine learning-based models and cloud computing applications could bring several benefits to the health care sector.…”
Section: Related Workmentioning
confidence: 99%